Fluid Origin and Evolution of the Roc Blanc Silver Deposit (Jebilet Massif, Variscan Belt, Morocco): Constraints from Geology and Fluid Inclusions - Amal El Arbaoui; Ismaïla N’Diaye; Zaineb Hajjar; Amina Wafik; Abdelhak Boutaleb; Said Ilmen; Abderrahim Essaifi; Mohammed Bouabdellah (Geofluids)
The Roc Blanc Pb-Zn-Ag-Au vein deposit is located in the NW of Marrakech, in the Central Jebilet massif. It is spatially related to Bramram-Tabouchennt-Bamega (BTB) granodioritic pluton (ca. 330 Ma) metamorphism aureole. The main veins hosted in black shales are oriented N-S to NNW-SSE. Pb-Zn-Ag-Au ore is associated with quartz, chlorite, sericite, and carbonate gangue minerals. Two major stages of ore deposition were distinguished. The preore stage (stage I) comprises two quartz-mineralised vein generations with Fe, As, Zn, and Cu ores (vg1 and vg2). The main ore stage (stage II) consists mainly on Ag, Au, Pb, Zn, Cu, and Sb ores, which is hosted by carbonaceous vein (vg3) and by two late quartz generations veins (vg4 and vg5 with a geodic quartz). Three types of fluid inclusions have been recognized in silver mineralisation bearing quartz veins according to petrographic investigations, microthermometry, and Raman spectroscopy studies: (i) liquid-rich H2O-N2-CH4±CO2-(salt) fluid inclusions (type 1), (ii) vapour-rich H2O-CO2-CH4-N2-(salt) fluid inclusions (type 2), and (iii) aqueous H2O-(salt) fluid inclusions (type 3). The interpretation of fluid inclusion data shows a mixing of two fluids that are metamorphic and surface to subsurface origin, trapped at boiling state. The first mineralised stage was deposited at 350±20°C (this temperature of ore deposition was supported also by chlorite geothermometry) with salinity of 13.7 wt% NaCl equiv., while the deposition of the argentiferous stage, which consists of the main economic mineralisation of the Roc Blanc deposit, occurs during decreasing temperature at 150°C with a salinity of 12.1 wt% NaCl equiv. The all-mineralised ore was deposited at relatively low pressure, below ~1-1.1 kbar. So, fluid dilution and cooling are probably the main factor for silver deposition in the Roc Blanc polymetallic vein deposit. In addition, fluid inclusion studies reveal that the mineralising fluid corresponds to a mixture of metamorphic fluid (H2O-CH4-N2-CO2) with surface to subsurface aqueous gas-free fluids (H2O-salt, meteoric, or brine).